High-heat-resistance lithium ion battery diaphragm and preparation method thereof
By applying a composite coating on the lithium-ion battery separator, the poor performance of traditional separators under high energy density and high safety requirements is solved, and the thickness uniformity and heat resistance of the separator are significantly improved, ensuring the safety performance of the battery.
Patent Information
- Application Number
- CN202510347879.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-24
AI Technical Summary
Traditional lithium-ion battery separators perform poorly under high energy density and high safety requirements, especially polyethylene (PE) and polypropylene (PP) separators have high surface energy, resulting in insufficient coating bonding strength and easy coating peeling, affecting the thickness uniformity and heat resistance of the separator.
A polyolefin base film is used as the base film and a composite coating is coated on its single or double-sided surface. The composite coating consists of ceramic particles, ethylene-vinyl acetate copolymer-type aqueous adhesive, crosslinking agent, polyacrylate-type aqueous adhesive, thickener, dispersant, wetting agent and deionized water. By configuring a thickened adhesive solution, the bonding force between the ceramic particles and the base film is improved, ensuring that the ceramic particles are firmly adhered to and preventing the coating from falling off.
It significantly improves the thickness uniformity and heat resistance of the lithium-ion battery separator, enhances the adhesion and mechanical properties of the separator, and ensures the safety performance of the battery.
Smart Images

Figure CN119864599A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery separator technology, and in particular to a lithium-ion battery separator with high heat resistance and its preparation method. Background Technology
[0002] As a key technology in the new energy field, the performance and safety of lithium-ion batteries have always been a research hotspot. The separator, a crucial component of the battery, plays a vital role in isolating the positive and negative electrodes, preventing short circuits, and allowing lithium ions to pass through. With the rapid development of electric vehicles and portable electronic devices, the demands on battery performance are constantly increasing, and traditional polyolefin separators are no longer sufficient to meet the requirements of high energy density and high safety. Coated separator technology has emerged to address this need. By coating a base membrane with specific materials, such as inorganic ceramics, glass fibers, or solid electrolytes, the thickness uniformity, thermal stability, mechanical strength, and puncture resistance of the separator are effectively improved. In particular, coated separators can significantly reduce the safety risks of batteries under extreme conditions, such as thermal runaway caused by high temperatures. Furthermore, the introduction of coating materials also helps improve the wettability of the separator, thereby improving the charge-discharge performance and cycle life of the battery.
[0003] Patent CN 110048057 A discloses a surface-modified PMMA / PVDF hybrid coated lithium-ion battery composite separator and its preparation method. This invention aims to provide a surface-modified PMMA / PVDF hybrid coated lithium-ion battery composite separator and its preparation method that effectively solves the problems of insufficient PVDF adhesion and the influence of crystallinity on ionic conductivity, while also improving the uniformity of PMMA electrolyte wetting. Furthermore, this invention also solves the problems of uneven mixing and easy sedimentation of PMMA and PVDF. However, polyethylene (PE) and polypropylene (PP) separators have high surface energies, making it difficult for these materials to be firmly coated onto the separator surface, resulting in insufficient bonding strength after coating and easy coating peeling. This phenomenon ultimately leads to uneven separator thickness and decreased heat resistance, potentially causing battery safety issues. Summary of the Invention
[0004] To overcome the aforementioned problems in the prior art, this invention provides a lithium-ion battery separator with high heat resistance and its preparation method. This separator exhibits low thermal shrinkage, enhanced adhesion, and improved mechanical properties, significantly improving the thickness uniformity and stability of the coated separator, thereby enhancing the safety performance of the lithium battery.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A high heat-resistant lithium-ion battery separator is composed of a polyolefin-based film and a composite coating applied to one or both sides of the film; the composite coating comprises, by weight, 20-40 parts ceramic particles, 1-4 parts ethylene-vinyl acetate copolymer water-based adhesive, 0.01-0.3 parts crosslinking agent, 1-8 parts polyacrylate water-based adhesive, 0.1-3 parts thickener, 1-3% of the weight of ceramic particles as dispersant, 0.1-0.5 parts wetting agent, and 70-100 parts deionized water; The ethylene-vinyl acetate copolymer waterborne adhesive is a copolymer emulsion of 40-80% vinyl acetate, prepared by polymerization reaction. By weight, it includes: 100-150 parts of deionized water, 2-10 parts of nonionic emulsifier, 0.1-0.5 parts of initiator, 0.1-0.5 parts of stabilizer, and 100 parts of a mixture of ethylene and vinyl acetate, wherein the molar ratio of ethylene to vinyl acetate is 1:0.67 to 1:4.
[0006] Because PE and PP membranes have high surface energy, ceramic particles coated on the membrane surface do not adhere easily, resulting in poor bonding strength with the base membrane and easy powdering, which increases the difficulty of coating the slurry on the surface. Therefore, before coating the slurry, this invention prepares a thickening adhesive solution and uniformly coats it onto the surface of the polyolefin base membrane. The thickening effect of the adhesive improves the bonding force between the ceramic particles and the base membrane, allowing the ceramic particles to adhere firmly to the membrane surface and preventing them from falling off. At the same time, the addition of the thickening adhesive solution also improves the fluidity of the coating, making the coating more uniform during the coating process and avoiding the problem of uneven coating.
[0007] Preferably, the ceramic particles are selected from one or more of alumina, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide and barium oxide, with an average particle size of 0.5-0.8 μm and a coating thickness of 1.5-3 μm.
[0008] Preferably, the nonionic emulsifier is selected from one or a mixture of polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene alkyl alcohol ethers, and polyoxyethylene alkylphenols in any proportion.
[0009] Preferably, the crosslinking agent is selected from one or a mixture of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) and dicumyl peroxide (DCP) in any proportion.
[0010] Preferably, the thickener is a carboxymethyl cellulose (CMC) thickener.
[0011] Preferably, the dispersant is selected from one or more of triethylhexylphosphoric acid, polyethylene glycol, polyvinyl alcohol, polyacrylate or cellulose derivatives, and its commonly used brands are BYK2010 and BYK9151 from BYK Chemicals, Germany.
[0012] Preferably, the wetting agent is an aqueous wetting agent selected from one or more of polyether-modified organosilicon, sodium butylnaphthalene sulfonate, and polyols, with the commonly used brand name being BYK-996.
[0013] The present invention also provides a method for preparing the above-mentioned lithium-ion battery separator, comprising the following steps: according to the raw material formula of the composite coating, the ceramic particles, ethylene-vinyl acetate copolymer (EVA) type aqueous adhesive, crosslinking agent, polyacrylate type aqueous adhesive, thickener, dispersant, wetting agent and water are mixed to prepare the composite coating, the composite coating is applied to a polyolefin base film and dried.
[0014] Preferably, the preparation process of the composite coating includes: step one, preparing a thickener aqueous solution; step two, preparing an EVA-type water-based adhesive; step three, preparing a thickening adhesive solution; and step four, adding ceramic particles, thickening adhesive solution, crosslinking agent, dispersant, wetting agent, and deionized water into a material tank and dispersing at high speed for 20-30 minutes to obtain the composite coating.
[0015] Preferably, step one, the preparation process of the thickener aqueous solution, includes: Weigh deionized water and thickener and add them to the tank. Use an electric high-speed disperser to disperse the thickener so that it can be uniformly dissolved in the deionized water to obtain a thickener aqueous solution.
[0016] Step Two: The preparation process of the ethylene-vinyl acetate copolymer waterborne adhesive includes: S 1: Add 100-150 parts by weight of deionized water and 2-10 parts by weight of nonionic emulsifier to the reaction vessel and stir until uniform; S 2: Add 0.1-0.5 parts by weight of initiator and 0.1-0.5 parts by weight of stabilizer, stir for 0.5-2 hours until the solution is homogeneous to form an initiator solution; S 3: Mix ethylene and vinyl acetate in a molar ratio of 1:0.67 to 1:4 (total mass parts of the mixture are 100 parts) and add them to the reactor. Heat the reactor to the set temperature of 60-80°C and stir continuously for 3-18 hours under nitrogen protection to complete the polymerization reaction. S 4: After the polymerization reaction is complete, stop heating and wait for the reaction system to cool to room temperature; S 5: Filter the reaction product to remove unreacted monomers and impurities, and adjust the pH of the emulsion to neutral to obtain a copolymer emulsion with a vinyl acetate content of 40-80%.
[0017] Step 3: The process of preparing the thickening adhesive solution includes: S 1: Weigh the thickener aqueous solution, EVA-type water-based adhesive, and polyacrylate-type water-based adhesive and add them to the tank; S 2: Use a high-speed disperser to disperse evenly, so that the two adhesives are evenly dispersed in the thickener aqueous solution, wherein the molecular chains of the adhesive and the thickener are intertwined to form a thickened adhesive solution.
[0018] Step 4: The process of preparing the composite coating includes: S 1: Weigh the dispersant, wetting agent and deionized water and add them to the tank. Use an electric high-speed disperser to disperse them evenly for 15-20 minutes to ensure that the dispersant and wetting agent are evenly dispersed in the deionized water medium to obtain a premixed liquid. S 2: Add ceramic particles to the premixed liquid and disperse at high speed for 20-30 min, so that the ceramic particles are fully adsorbed on the surface by the dispersant to form a ceramic dispersion with good uniformity. S 3: Add thickening binder and crosslinking agent, and continue high-speed dispersion for 20-30 min to obtain composite coating.
[0019] Preferably, the prepared composite coating is applied to one or both sides of the polyolefin-based film and dried with hot air; the hot air temperature is controlled at 100℃-120℃ and the drying time is 3min-4min.
[0020] Therefore, the present invention has the following beneficial effects.
[0021] (1) By precisely controlling the raw material ratio, an ethylene-vinyl acetate copolymer-type waterborne adhesive with a vinyl acetate content ranging from 40% to 80% was prepared. This type of adhesive is rich in ester functional groups and exhibits excellent molecular chain flexibility. When mixed with thickeners containing abundant hydroxyl functional groups and polyacrylate adhesives, they preferentially form hydrogen bonding and intermolecular forces. This interaction promotes the entanglement of molecular chains, thereby forming a stable compatibility state.
[0022] (2) When the ethylene-vinyl acetate copolymer water-based adhesive, polyacrylate adhesive and thickener are entangled in the coating, and under the action of crosslinking agent and high temperature, they can penetrate into the molecular chains of PE or PP membrane to form a three-dimensional network structure. This process significantly improves the adhesion between the coating and the surface of PE or PP membrane.
[0023] (3) Through the synergistic effect of ceramic particles and high heat-resistant polypropylene adhesive, the heat resistance of the diaphragm is significantly improved. This not only enhances the heat shrinkage resistance of the diaphragm, but also ensures its safety in high-temperature environments.
[0024] Therefore, the separator is not easily deformed during battery use, which helps prevent battery safety hazards. Attached Figure Description
[0025] Figure 1 This is a SEM image of the lithium-ion battery separator according to an embodiment of the present invention.
[0026] 1. Coating; 2. PP diaphragm. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0028] Example 1 This embodiment provides a method for preparing a lithium-ion battery separator, including the following steps: According to the raw material formula of the composite coating, the ceramic particles, ethylene-vinyl acetate copolymer (EVA) type waterborne adhesive, crosslinking agent, polyacrylate type waterborne adhesive, thickener, dispersant, wetting agent and water are mixed to prepare the composite coating, and the composite coating is applied to a polyolefin base film and dried.
[0029] Step 1: Prepare a thickener aqueous solution Weigh 98.00 g of deionized water and 2.00 g of thickener and add them to a container. Disperse the mixture using a high-speed disperser at 600 rpm / min for 24 h. This ensures that the thickener is uniformly dissolved in the deionized water, resulting in a thickener aqueous solution with a 2% solids content.
[0030] Step 2: Preparation of EVA-type waterborne adhesive S1: Add 100.00 g of deionized water and 4.00 g of polyoxyethylene alkyl alcohol ether to the reactor. Stir for 0.5 h until the solution is homogeneous; S 2: Add 0.20 g of potassium persulfate and 0.20 g of sodium hydroxide to the reaction vessel, stir for 1 h until the solution is homogeneous to form an initiator solution; S 3: Mix ethylene and vinyl acetate in a molar ratio of 1:1.5 (100 g by mass) and add the mixture to the reactor. Heat the reactor to the set temperature of 65°C and carry out the polymerization reaction by stirring continuously for 12 h under nitrogen protection. S 4: When the polymerization reaction reaches the predetermined time, stop the reaction and cool the reaction system to room temperature; S 5: Filter the reaction product to remove unreacted monomers and impurities, and adjust the pH of the emulsion to neutral to obtain an EVA copolymer emulsion with a VA content of 40%.
[0031] Step 3: Prepare a thickening adhesive solution Weigh 50.00 g of a 2% solids content thickener aqueous solution, 4.00 g of an EVA copolymer emulsion with 40% VA content, and 5.00 g of a polyacrylate-based aqueous adhesive, add them to a container, and disperse them evenly using a high-speed disperser at 1500 rpm / min for 1.5 h. This ensures that the two adhesives are uniformly dispersed in the thickener aqueous solution, where the molecular chains of the adhesive and thickener become entangled, thus forming a thickened adhesive solution.
[0032] Step 4: Prepare the paint S1: Weigh out 0.20 g of dispersant BYK 9151, 0.12 g of wetting agent, and 50.00 g of deionized water and add them to the tank. Disperse the mixture at 1500 rpm for 15 min using a high-speed disperser. This ensures that the dispersant and wetting agent are uniformly dispersed in the deionized water medium, resulting in a premixed solution. S 2: Add boehmite particles (20.00 g) (particle size 0.5 μm) to the premix and disperse at high speed (1500 rpm / min) for 30 min. This allows the ceramic particles to be fully adsorbed onto the surface by the dispersant, forming a ceramic dispersion with good uniformity. S3: Finally, add the thickening binder prepared in step three and 0.10 g of crosslinking agent, and continue high-speed dispersion at 1500 rpm / min for 30 min to obtain the coating.
[0033] Step 5: Coating The coating was applied to the PP membrane (18μm) using a wire bar coater and dried in an oven with hot air (120℃, 5 min) to promote moisture evaporation and cross-linking reaction. The coating thickness after drying was 4μm, resulting in a single-layer coated membrane with a thickness of 18+4μm.
[0034] Example 2 The only difference from Example 1 is that the amount of ceramic particles used in the composite coating is 30.00 g.
[0035] Example 3 The only difference from Example 1 is that the amount of ceramic particles used in the composite coating is 40.00 g.
[0036] Example 4 The only difference from Example 1 is that the amount of ethylene-vinyl acetate copolymer water-based adhesive used in the composite coating is 1.00 g.
[0037] Example 5 The only difference from Example 1 is that the amount of ethylene-vinyl acetate copolymer water-based adhesive used in the composite coating is different, at 2.00 g.
[0038] Example 6 The only difference from Example 1 is that the amount of ethylene-vinyl acetate copolymer water-based adhesive used in the composite coating is different, at 3.00 g.
[0039] Example 7 The only difference from Example 1 is that the amount of polyacrylate-based water-based adhesive used in the composite coating is 1.00 g.
[0040] Example 8 The only difference from Example 1 is that the amount of polyacrylate-based water-based adhesive used in the composite coating is 8.00 g.
[0041] Example 9 The only difference from Example 1 is that the vinyl acetate content of the ethylene-vinyl acetate copolymer water-based adhesive is different, and the VA content is 50% of the EVA copolymer emulsion.
[0042] Example 10 The only difference from Example 1 is that the vinyl acetate content of the ethylene-vinyl acetate copolymer water-based adhesive is different, and the VA content is 60% of the EVA copolymer emulsion.
[0043] Example 11 The only difference from Example 1 is that the vinyl acetate content of the ethylene-vinyl acetate copolymer water-based adhesive is different, and the VA content is 70% of the EVA copolymer emulsion.
[0044] Example 12 The only difference from Example 1 is that the vinyl acetate content of the ethylene-vinyl acetate copolymer water-based adhesive is different, and the VA content is 80% of the EVA copolymer emulsion.
[0045] Comparative Example 1 Uncoated ordinary PP membrane.
[0046] Comparative Example 2 The only difference from Example 1 is that the composite coating does not contain an ethylene-vinyl acetate copolymer type water-based adhesive.
[0047] Comparative Example 3 The only difference from Example 1 is that the composite coating does not contain polyacrylate adhesive.
[0048] The lithium battery separators prepared in the above embodiments and comparative examples were cut to A4 size, and their performance was tested. The results are shown in Table 1. The test methods are as follows: (1) Average thickness: The thickness of the coated diaphragm at different locations was measured using a micrometer screw gauge, and the average value was calculated; (2) Heat resistance test: The heat resistance of the diaphragm is characterized by the heat shrinkage rate. The test is conducted according to the test method for heat shrinkage rate in the national standard GB / T-36363-2018. The instrument used is a forced-air drying oven. (3) Tensile strength test: The test shall be conducted in accordance with the test method for tensile strength in the national standard GB / T-36363-2018; (4) Ionic conductivity test: The assembly method of steel sheet / diaphragm / steel sheet was adopted. The bulk resistance was tested using the electrochemical impedance spectroscopy (EIS) mode of VMP 3 B-10 electrochemical workstation (Bio-Logic Science Instruments). The perturbation voltage amplitude was 5 m V and the frequency was 10 m Hz to 1 MHz. The relationship between bulk resistance and ionic conductivity is calculated as follows: Ionic conductivity = diaphragm thickness / (diaphragm resistance * contact area between diaphragm and electrode) * 10-2, where the unit of diaphragm thickness is mm, the unit of diaphragm resistance is Ω, and the unit of contact area between diaphragm and electrode is m2. (5) Peel strength test: The test shall be conducted in accordance with the method in GB / T 2792-2014 Peel strength of adhesive tape, and the instrument used shall be a universal testing machine.
[0049] Table 1. Summary of performance test results of battery separators prepared in Examples 1-12 and Comparative Examples 1-3.
[0050] As can be observed from the data in Table 1, compared to Comparative Example 1, i.e., the uncoated PP diaphragm, the diaphragms prepared in Examples 1-3 and Example 8 of this invention exhibit significantly improved heat resistance thanks to the synergistic effect of the ceramic particles and the high-heat-resistant polypropylene adhesive. This indicates that the introduction of the coating enhances the diaphragm's resistance to heat shrinkage and ensures its safety in high-temperature environments.
[0051] By comparing Examples 1 with Examples 4-6, Examples 9-12, and Comparative Example 2, it is evident that the adhesion of Examples 1 and 9-12 is significantly greater than that of Comparative Example 2. This indicates that a stable compatibility significantly enhances the bonding strength between the coating and the substrate. Further observation of Examples 4-6 reveals that their mechanical properties (including thermal shrinkage and tensile strength) are also superior to Comparative Example 2. This is attributed to the abundance of ester functional groups in the adhesive, which endows it with excellent molecular chain flexibility. These ester functional groups form hydrogen bonds and intermolecular forces with the thickener containing hydroxyl functional groups and the polyacrylate adhesive, promoting the entanglement of molecular chains and thus forming a stable compatibility. This compatibility not only significantly enhances the adhesion and mechanical properties of the coating but also improves its overall stability. In contrast, Comparative Example 2, lacking sufficient ester and hydroxyl functional groups, cannot effectively form hydrogen bonds and intermolecular forces, resulting in poor compatibility and consequently reduced performance.
[0052] By comparing Examples 1 with Examples 7 and 8 and Comparative Example 3, it is evident that due to the polyacrylate adhesive, the ethylene-vinyl acetate copolymer water-based adhesive and thickener are entangled in the coating. Under the action of the crosslinking agent and high temperature, they can penetrate into the molecular chains of the PE or PP membrane, forming a three-dimensional network structure. This significantly improves the adhesion between the coating and the surface of the PE or PP membrane.
[0053] Comparative analysis with Examples 7 and 8: In Examples 7 and 8, the adhesion of the coating was not as good as in Example 1 due to the use of different amounts of polyacrylate adhesive. This indicates that in Example 1, the amount of polyacrylate adhesive was more effective in bonding with the PE or PP membrane.
[0054] A comparison with Comparative Example 3 shows that, since Comparative Example 3 did not use a polyacrylate adhesive, its coating adhesion was significantly lower than that of Example 1. This further confirms the significant advantage of polyacrylate adhesives in enhancing the adhesion of coatings to PE or PP membranes.
Claims
1. A high heat-resistant lithium-ion battery separator, characterized in that: The invention is composed of a polyolefin base film and a composite coating applied on one or both sides thereof; the composite coating comprises, by weight, 20-40 parts of ceramic particles, 1-4 parts of ethylene-vinyl acetate copolymer type water-based adhesive, 0.01-0.3 parts of a cross-linking agent, 1-8 parts of a polyacrylate type water-based adhesive, 0.1-3 parts of a thickener, 1-3% of the weight of the ceramic particles in a dispersant, 0.1-0.5 parts of a wetting agent and 70-100 parts of deionized water; The ethylene-vinyl acetate copolymer type water-based adhesive is a copolymer emulsion of 40-80% vinyl acetate, which is prepared by polymerization reaction and includes, by weight: 100-150 parts of deionized water, 2-10 parts of non-ionic emulsifier, 0.1-0.5 parts of initiator, 0.1-0.5 parts of stabilizer and 100 parts of ethylene and vinyl acetate mixture, wherein the molar ratio of ethylene to vinyl acetate is 1:0.67~1:
4.
2. A high heat-resistant lithium-ion battery separator according to claim 1, characterized in that: The ceramic particles are selected from one or more of aluminum oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide and barium oxide, with an average particle size of 0.5-0.8 μm and a coating thickness of 1.5-3 μm.
3. The high heat-resistant lithium-ion battery separator according to claim 1, characterized in that: The nonionic emulsifier is selected from one of polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene alkyl alcohol ethers, polyoxyethylene alkyl phenols, or a mixture in any proportion; And or, the cross-linking agent is selected from tert-butyl peroxycarbonate-2-ethylhexyl ester, diisopropylbenzene peroxide, or a mixture in any proportion; And / or, the thickener is a carboxymethyl cellulose thickener; and / or, the dispersant is selected from one or more of triethylhexyl phosphoric acid, polyethylene glycol, polyvinyl alcohol, polyacrylate or cellulose derivatives; And / or, the wetting agent is a water-based wetting agent selected from one or more of polyether-modified silicones, sodium butylnaphthalene sulfonate and polyols.
4. The high heat-resistant lithium-ion battery separator according to claim 1, characterized in that: The polyolefin-based film is selected from at least one of a PP diaphragm and a PE diaphragm; And / or, the thickness of the polyolefin-based film is 6 μm-20 μm, and the thickness of the composite coating is 2 μm-6 μm.
5. A method for preparing a high heat-resistant lithium-ion battery separator according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: according to the raw material formula of the composite coating, the ceramic particles, ethylene-vinyl acetate copolymer type water-based adhesive, a crosslinking agent, a polyacrylate type water-based adhesive, a thickener, a dispersant, a wetting agent and water are mixed to prepare a composite coating, the composite coating is coated on a polyolefin base film, and then dried.
6. The method for preparing a high heat-resistant lithium-ion battery separator according to claim 5, characterized in that: The preparation process of the composite coating comprises: S1: preparing a thickener aqueous solution; S2: preparing an ethylene-vinyl acetate copolymer type water-based adhesive; S 3: Prepare a thickening adhesive solution; S 4: Add ceramic particles, thickening adhesive solution, crosslinking agent, dispersant, wetting agent, and deionized water into a material tank, and disperse at high speed for 20-30 minutes to obtain a composite coating.
7. The method for preparing a high heat-resistant lithium-ion battery separator according to claim 6, characterized in that: The step S2: the preparation process of the ethylene-vinyl acetate copolymer type water-based adhesive comprises: S1: Add 100-150 parts by mass of deionized water and 2-10 parts by mass of nonionic emulsifier into the reaction kettle and stir until uniform; S 2: adding 0.1-0.5 parts by mass of an initiator and 0.1-0.5 parts by mass of a stabilizer, stirring for 0.5-2 hours until the solution is uniform, to form an initiator solution; S3: Ethylene and vinyl acetate are mixed in a molar ratio of 1:0.67 to 1:4, and the total weight of the mixture is 100 parts, and the mixture is added into a reactor, and the reactor is heated to a set temperature of 60-80° C., and under nitrogen protection, stirring is continued for 3-18 hours to complete the polymerization reaction; S4: After the polymerization reaction is completed, stop heating and wait for the reaction system to cool to room temperature; S 5: filtering the reaction product to remove unreacted monomers and impurities, and adjusting the pH value of the emulsion to neutral, thereby obtaining a copolymer emulsion having a vinyl acetate content of 40-80%.
8. The method for preparing a high heat-resistant lithium-ion battery separator according to claim 6, characterized in that: The process of step S3: preparing the thickening adhesive solution comprises: S 1: weigh the thickener aqueous solution, EVA type water-based adhesive, polyacrylate type water-based adhesive and add them to the material tank; S2: Use a high-speed disperser to disperse the two adhesives evenly in the thickener aqueous solution, wherein the molecular chains of the adhesive and the thickener are entangled with each other to form a thickened adhesive solution.
9. The method for preparing a high heat-resistant lithium-ion battery separator according to claim 6, characterized in that : The process of step S4: configuring the composite coating comprises: S 1: Weigh the dispersant, wetting agent and deionized water and add them to the material tank, use an electric high-speed disperser to disperse evenly at high speed for 15-20 min, so that the dispersant and wetting agent are evenly dispersed in the deionized water medium to obtain a premix; S 2: Add ceramic particles to the premixed liquid and disperse at high speed for 20-30 min, so that the ceramic particles are fully adsorbed on the surface by the dispersant to form a ceramic dispersion with good uniformity; S 3: Add thickening binder and crosslinking agent, and continue high-speed dispersion for 20-30 min to obtain a composite coating.
10. The method for preparing a high heat-resistant lithium-ion battery separator according to claim 6, characterized in that: Applying the composite coating on one or both sides of the polyolefin base film and drying it with hot air; Control the hot air temperature to 100℃-120℃ and the drying time to 3 min-4 min.
Citation Information
Patent Citations
Surface-modified PMMA / PVDF hybrid-coated lithium battery composite diagram and preparation method thereof
CN110048057A
Integrated ceramic-coated lithium battery diaphragm and preparation method thereof, and ceramic coating
CN111509170A
Functional coating diaphragm for lithium ion battery, and preparation method thereof
CN111509173A
Lithium ion battery diaphragm, lithium ion battery and preparation method of lithium ion battery diaphragm
CN113594633A
Method for preparing vinyl acetate-ethylene copolymer emulsion, vinyl acetate-ethylene copolymer emulsion and application of vinyl acetate-ethylene copolymer emulsion
CN118290641A